Climate Change Impacts on Coastal Vulnerability and Adaptation Readiness: Maritime Perspective - Arfin Trimedianto; Danang Marsudi; Faurna Lusiani P; Manahan Budiarto Panjaitan (Golden Ratio of Data in Summary, 2024)
Global climate change has caused serious impacts on coastal areas, including coastal erosion, infrastructure damage, and disruption of marine ecosystems. Sea-level rise and increased frequency and intensity of storms are major threats, exacerbating the economic and social vulnerabilities of coastal communities. In the face of these challenges, effective adaptation efforts and adequate policy support are essential to enhance community resilience. This study aims to explore the impacts of climate change on coastal vulnerability and assess the readiness and effectiveness of adaptation efforts from a maritime perspective. The main focus is on how sea-level rise, storms, and changes in marine ecosystems affect coastal communities, and identify the need for better policies and support for adaptation efforts. This study uses a qualitative approach by collecting primary data through in-depth interviews with coastal community members. Secondary data are also used to complement information related to climate change impacts and adaptation efforts. Data collection techniques include field observations and semi-structured interviews. Data analysis is carried out systematically with coding, categorization, and interpretation steps to identify key patterns and themes. Key findings indicate that the impacts of climate change on coastal areas are extensive. Sea-level rise causes coastal erosion and land loss that impact agriculture and settlements, while increased frequency and intensity of storms result in major damage to infrastructure and economic losses. Impacts on marine ecosystems include coral bleaching and declines in fish species, as well as the impacts of ocean acidification on marine life. Adaptation efforts include seawall construction, mangrove restoration, and community education programs, but are often limited by funding and technical support. The study also identified an urgent need for more comprehensive adaptation policies and additional financial and technical support to improve the effectiveness of future adaptation strategies.